A REVIEW ON PRODUCTION OF PCDNA3.1-EGFP WITH CLONING PRINCIPLE METHOD - Margiana, Ria (Asian Journal of Pharmaceutical and Clinical Research, 2016)
ABSTRACT pcDNA3.1-e green fluorescent protein (GFP) is an important compound that is already established and widely used as a marker in biomolecular works. Producing pcDNA3.1-eGFP is not very complicated. It can be inserted to Escherichia coli and replicate in millions. Due to the availability of E. coli is in Indonesia, this process should not be difficult at all. A description of the method of producing pcDNA3.1-eGFP will be covered so that many Indonesian and other researchers as well can use it and develop it in their own research. The production of pcDNA3.1-eGFP has been done by several researchers around the globe. In this review article, five relevant studies have been included. Their respective results were analyzed. The pcDNA3.1 can be expressed differently apart from the eGFP form. Therefore, it can serve different purposes, especially when the different cloning and sub-cloning processes are involved. It can be used to improve outcomes in various fields such as veterinary science, health, wellness, medicine, and even agriculture. Through the use of the cloning principle, mass production of pcDNA3.1-eGFP can be carried out easily. Keywords: pcDNA3.1-Green fluorescent protein, Cloning, Escherichia coli.